2020
DOI: 10.1108/jhr-01-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding challenges among Thai adolescent mothers: hidden breastfeeding discontinuation experiences

Abstract: PurposeThe purpose of this study was to explore the experiences of adolescent mothers who wean their babies from breastfeeding before the first six months from the perspective of a psychosocial aspect in the Thai context.Design/methodology/approachA descriptive qualitative design was applied to this study to obtain meaningful data. The adolescent mothers for the primary study and nine supplementary participants were recruited from the largest university hospital in Bangkok, Thailand. Semi-structured in-depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…Unsurprisingly, several previous studies have reported positive associations between exclusive breastfeeding and adequate maternal knowledge of the benefits of exclusive breastfeeding, positive attitude toward breastfeeding [ 54 ], social support from friends and family [ 52 , 56 , 57 ], and peer counselling on exclusive breastfeeding [ 54 , 57 ], which is consistent with our results. For example, in 2018, a meta-analysis of 27 randomised controlled trials found that mothers with breastfeeding support were more likely to practice exclusive breastfeeding than those without support [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unsurprisingly, several previous studies have reported positive associations between exclusive breastfeeding and adequate maternal knowledge of the benefits of exclusive breastfeeding, positive attitude toward breastfeeding [ 54 ], social support from friends and family [ 52 , 56 , 57 ], and peer counselling on exclusive breastfeeding [ 54 , 57 ], which is consistent with our results. For example, in 2018, a meta-analysis of 27 randomised controlled trials found that mothers with breastfeeding support were more likely to practice exclusive breastfeeding than those without support [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, in line with our findings, a Brazilian systematic review of 27 studies found that teenage mothers were less likely to practise exclusive breastfeeding [ 55 ]. Younger mothers may have a lower exclusive breastfeeding rate due to a possible lack of awareness of the benefits of exclusive breastfeeding, inadequate breastfeeding skills, and unpleasant and painful breastfeeding experiences [ 56 59 ]. Young mothers often introduce complementary foods earlier than recommended to avoid the unpleasant experiences and perceived physical changes associated with exclusive breastfeeding [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative analysis of this study also showed that in this new pandemic context of the postpartum period, that spousal support was important, and spouses provided emotional and tangible support to postpartum mothers. On the other hand, the social distancing for nuclear families provided mothers the opportunity to try novel mothering styles because of the reduced the influence of older generations on infant feeding [ 56 , 57 ]. Mothers who exclusively breastfeed felt that the mitigation strategies had positive effects on their breastfeeding practices because they had more time to breastfeed, recognized the economic benefits, got more support from their spouse, and some of the typical social obstacles were removed.…”
Section: Discussionmentioning
confidence: 99%
“…More time spent at home during the COVID-19 pandemic was positively correlated with breastfeeding ( Rimawati & Suwardianto, 2020 ). Accordingly, the main source of support for postpartum mothers during COVID-19 was spouses or partners, which might prevent early supplementary food that comes from the traditional beliefs of grandmothers ( Nuampa et al, 2022 ; Vazquez-Vazquez et al, 2021 ). These results differed from a pre-pandemic study in the United Kingdom, where instrumental support from family—including help with household labor, childcare, or finances—and emotional support were associated with longer breastfeeding duration ( Emmott et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%